Synthesis and Liquid Crystalline Behavior of New Amides and Esters Containing 1,3- Thiazole Ring - Karam, Nisreen H; Tomma, Jumbad H; AL-Dujaili, Ammar H; Jber, Nasreen R (Al-Nahrain Journal of Science, 2018)
Synthesis and study liquid crystalline properties of new compounds with terminal groups of amides ([III]a-c,[IV]a-c and [VI]n), alkoxy series[V]n or ester with azo linkage ([IX]a-c and[X]a-c) containing thaizole ring. These series were synthesized by many steps starting from 4- hydroxyacetophenone or 4-aminoacetophenone.The synthesized compounds were characterized using melting points, FTIR, C.H.N.S analysis and for some of them 1H NMR spectroscopy. The liquid crystalline properties were studied by hot stage polarizing microscopy and differential scanning calorimetry DSC. All compounds of series [III]a-c,[IV]a-c and compounds [V]n showed enantiotropic liquid crystal. While the series [VI]n showed nematic mesomorphism except [VI]8 did not show any mesomorphic behavior, also the compounds [IX]a, b and [X]a, b showed nematic liquid crystalline, but the compounds[IX]c and [X]c did not show any liquid crystalline properties.